2013
DOI: 10.1094/fg-2013-0326-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Irrigation and Nitrogen Treatments Slightly Affected Teff Yield and Quality in the Southwestern USA

Abstract: Interest exists in using teff [Eragrostis tef (Zucc.) Trotter] for horse hay in the southwestern USA. Randomized complete block studies in 2007 and 2008 at New Mexico State University's Agricultural Science Center at Tucumcari compared teff forage yield and quality when all or alternate furrows were irrigated (full or limited irrigation, respectively) after the first harvest, with nitrogen treatments [60 or 90 lb N/acre preplant (Single60 and Single90, respectively) and 30 lb N/acre preplant and after the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Canopy height comparisons were based on 10 physically-measured canopy height classes at ten centimeter increments. These comparisons were performed using PROC MIXED [ 34 ] in combination with the PDMIX800 macro [ 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…Canopy height comparisons were based on 10 physically-measured canopy height classes at ten centimeter increments. These comparisons were performed using PROC MIXED [ 34 ] in combination with the PDMIX800 macro [ 41 , 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…At the study site, optimum temperature for teff production can be observed from April to June and September, while temperatures are higher than optimum from July to August (Table 1). Typically, the first harvest of teff averaged 68 DAP (range: 48–95 DAP) with subsequent harvest at an average of 38 days (range: 25–48 days after harvest [DAH]) (Hall & Cherney, 2010; Hancock & Durham, 2009; Lauriault et al., 2014; Roseberg et al., 2005). The average DAP and DAH for the present study were 64 DAP with cut 2 at 42 DAH and cut 3 at 53 DAH.…”
Section: Resultsmentioning
confidence: 99%
“…Roseberg et al (2005) reported no nitrogen response of teff under little or no irrigation in Oregon. Most studies reported no yield advantages with nitrogen rates greater than 50 lb a −1 cut −1 (Abaye et al, 2009;Hancock et al, 2009;Hunter et al, 2009;Lauriault et al, 2014;Roseberg et al, 2005). The present study also showed the yield advantage with nitrogen application at 50 lb a −1 and not with 100 lb a −1 in dryland trial.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations